Budget Support Versus Project Aid - Cordella, Tito (IMF Working Papers; Working Paper ;, 2003)
Should donors who are interested in the effectiveness of developmental programs rely on conditional budget support or on project aid? To answer this question, we present a model in which only a subset of the developmental expenditures can be subject to conditionality. We show that budget support is preferable to project aid when donors and recipients' preferences are aligned, and when assistance is small relative to recipients' resources. Then, we test our model estimating a modified growth model for a panel of developing countries, and find evidence in support of our predictions.